EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PEMAHAMAN SISWA PADA PEMBELAJARAN IPS KELAS IV - Fenti Widiyana; Muhamad Idris; Erfan Ramadhani (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
The problem examined in this article is students’ low understanding of social sciences learning subjects on cultural diversity learning material. Hence, it is necessary for the researcher to make a study to find out whether the cooperative learning model is an alternative to improve students' understanding and is more effective to provide social sciences learning subjects for class IV at SDN 81 Palembang or not, especially on jigsaw implementation. The method used was a quantitative research method in the type of experimental research. Data collection instruments were used through tests, observations, and documentation. Based on the results, jigsaw as a cooperative learning model was effective to improve students' understanding of social sciences learning subjects for cultural diversity learning material in grade IV, with an average post-test in the experimental class (86.0) that was higher than the post-test in the control class (78.8). The t-test that was carried out after the teaching obtained a significant value. Therefore, the significant (2-tailed) value of the t-test results obtained a value of 0.000, which was less than 0.025 (0.000 < 0.025). Related to these data, it was found that jigsaw as a cooperative learning model was effectively applied in social sciences learning subjects and could improve students' understanding during the teaching and learning processes in the classroom.